A comparative study to assess thoracic kyphotic index in adults with and without mechanical neck pain - Khan, Amina Farid; Pervez, Munazza; Saif, Sania; Batool, Fouzia; Anjum, Huda; admin (Journal of the Pakistan Medical Association, 2023)
Objective: To assess thoracic kyphotic index in adults, and to find out the correlation between Neck Disability Index and Thoracic Kyphotic Index. Method: The analytical cross-sectional study was conducted from October 2020 to January 2021 at the Shifa Tameer-e-Millat University, Islamabad, Pakistan, and comprised adults aged 18-35 years. Those with neck pain formed group A, while those without neck pain formed group B. The Numeric Pain Rating Scale and the Neck Disability Index were used to measure mechanical neck pain, while the Thoracic Kyphotic Index value was measured using a flexicurve ruler. Data was analyzed using SPSS 24. Results: Of the 74 subjects, 37(50%) were in each of the two groups. There were 19 (51.40%) females and 18(48.60%) males in group A, while in group B there were 18(48.60%) females and 19(51.40%) males. The overall mean age of the sample was 23.35±3.31 years. Group A showed higher Thoracic Kyphotic Index value than group B (p=0.0001). The Neck Disability Index showed negative weak (r=-0.18, p=0.28) correlation with Thoracic Kyphotic Index in group B and moderate positive correlation (r=0.33, p=0.04) in group A. Conclusion: Higher Thoracic Kyphotic Index value was found among adults with mechanical neck pain compared to healthy adults. Key Words: Cross-sectional study, Female, Male, Neck pain, Pakistan, Young adult.